Germline pathogenic variants associated with ovarian cancer: A historical overview - Emma Lund Johansen; Christine Fribert Thusgaard; Mads Thomassen; Susanne Eriksen Boonen; Kirsten Marie Jochumsen (Elsevier, 2022)
The risk of ovarian, tubal, and peritoneal cancer is related to germline pathogenic variants, and over time, the number of known disease-associated genes has increased significantly. This study reviews the literature regarding the topic from a historical perspective. The aim is to present a timeline of the knowledge gained from the early 1900s until today. The findings are put into perspective by looking at the current gene panel used for screening for suspected hereditary ovarian cancer in Denmark compared to what is known internationally. In 1929, the first familial ovarian cancer incidents were registered, and in 1950, the involvement of a genetic component was suggested for the first time. During the 1970s, several studies reported an accumulation of ovarian cancer in certain families, and during this time, it was discovered that ovarian cancer was linked to both breast cancer and colorectal cancer. The inheritance of cancer disposition has been thoroughly investigated, leading to the discovery of the BRCA genes in the 1990s. Furthermore, new studies based on new genetic technologies have revealed several genes with germline pathogenic variants that increase the risk of ovarian cancer. The identification of these pathogenic variants has led to preventive measures and specific treatment of women with genetic disposition to ovarian cancer. In Denmark, consensus is to include at least ten genes in the screening panel for hereditary ovarian cancer, and in the future additional genes will probably be added.